Surviving against the tide: Are new businesses in innovative industries Less affected by general economic trends? - Michael Fritsch; Florian Noseleit; Yvonne Schindele (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
We investigate the role of industry and region-specific conditions for the survival of new businesses in innovative and in other manufacturing industries. The data comprises all German manufacturing start-ups of the 1992 to 2005 period. In contrast to studies for some other countries, we find that businesses in innovative industries have higher survival rates than businesses in other manufacturing industries. Moreover, the chances of survival for innovative industries are rather immune to changes, regarding regional and industry-specific conditions, whereas businesses in the other manufacturing industries are strongly affected. These findings highlight that resistance to adverse conditions is dependent on industry specific opportunities and technological conditions.
Keywords: C41; L25; L26; L60; 330; duration analysis; entrepreneurship; hazard rates; location; new business survival